Critical Modal Frequency in Quadcopters: An Analytical and Simulation-Based Arm Study - Lopez, T. Edward; Lostaunau, N. Oscar; Flores, O. Luis; Rivera, C. Mauricio; Jara, A. Elvis; Nuñez, O. Moises (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
This paper focuses on determining the natural frequencies of a drone through both analytical and simulation studies of the quadcopter. The analytical approach involves formulating the dynamic vibration model of the arm and the drone as a mass-spring system. For the simulation, the finite element method (FEM) is employed on the CAD model of the quadcopter, incorporating the mechanical properties of the materials used. The results were validated with experimental data obtained from a real high-load drone during flight. The study demonstrates that the arm natural frequencies obtained analytically and through simulation align with the real drone frequency data with accuracy of 76% and 84%, respectively. These findings suggest that the combined analytical and simulation approach for studying the drone’s arm is a simple and effective method for identifying critical natural frequencies in a quadcopter.